(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
Present paper deals with the occurrence and diversity of fungi on storage cotton (Gossypium hirsutum L.) seeds. 24 species of the fungi were found associated with the seeds of 14 varieties of cotton after 10 months of storage. The isolated fungi were Aspergillus flavus Link, A. fumigatus Fresenius, A. niger (Type 1 and Type 2) Van Tiegh, A. ochraceus K. Wilhelm, A. nidulans Eidam, Aspergillus sp.1, Aspergillus sp.2, Aspergillus sp.3, Curvularia lunata (Wakker) Boedijn, Colletotrichum gloeosporioides Penz & Sacc, C. gossypii Southw., Chaetomium globosum Kunze., Fusarium nivale (Fr.) Sorauer, F. moniliforme J. Shelden, F. oxysporum Schlechtendal, F. fujikuroi Nirenberg, Mucor sp. P. Micheli ex L., Penicillium sp.1 and sp.2 Link, Rhizoctonia solani Khun., Rhizopus stolonifer (Ehrenb.) Vuill., Rhizomucor Lucet & Costantin, Syncephalastrum racemosum Cohn and Trichoderma viride Pers. The association of fungi with cotton seeds was recorded within two months of harvest, after 6 and 10 months of storage. The association of fungi varied with duration of storage periods. Aspergillus flavus, A. fumigatus, A. niger, Chaetomium globosum, Penicillium sp.1 and Rhizopus stolonifer were found in all the examined varieties. These were the most predominant fungi in terms of prevalence with the increase of storage periods. The fungal association with the seeds of cotton also affected the germination, seedling mortality, height and vigor. The total association of fungi in cotton seeds was the highest in cotton variety CB10 (204) and the lowest in CB8 (71). On the other hand, the total fungal association of Rhizopus stolonifer was the highest (337) and Colletotrichum gossypii was the lowest (1). J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(2): 43-52